A Geometry Optimization of Spiral Grain Selector During Directional Solidification of Nickel‐Based Superalloy. Issue 9 (11th June 2022) - Wang, Binqiang; Zeng, Long; Li, Jianguo
Abstract: A spiral grain selector with excellent geometric parameters can ensure qualified single‐crystal (SX) is selected while decreasing lesser thermal gradient ( G ) during casting of SX nickel‐based superalloy . In this paper, three configurations of spiral grain selectors with different height of starter block ( H = 18, 25, 35 mm) and same spiral passage are adopted. Based on the quantitative analysis of orientation distribution of grains in starter block, it is found that the deviation of <001> oriented grains in the projection zone of spiral passage inlet (circle with a diameter of 4 mm) are smaller than grains of overall cross‐section (circle with a diameter of 10 mm), which verify that starter block with smaller diameter have better optimization effect of grain orientation. Moreover, the average deviation of <001> oriented grains decreases to a range of 6.6–10.8° when the height of starter block is 18–27 mm, and SX selection is completed on the position of less than half turn in spiral passage regardless of the number of grains in the inlet position. Finally, a modified spiral grain selector is designed from the perspective of practical production, of which total height is reduced by at least 15 mm, and can decrease lesser G at some extent during casting . Abstract : This paper reports that starter block with smaller diameter has better optimization effect of grain orientation during directional solidification of nickel‐based single‐crystal superalloy, and the single‐crystal appears at less than half‐turn position of spiral passage. Based on this, a spiral grain selector with optimized geometry is designed which is beneficial to practical production.